Educação ambiental e recursos hídricos: percepção dos estudantes do ensino público de Campina Grande, Paraíba - Santos, Thayanna Maria Medeiros (2019)
The growing technological development and scientific innovations of societies have stimulated consumerism and the disharmonious relationship with the environment. With this, several negative impacts are observed on the physical, biological and social environment. In this context, Environmental Education is fundamental, at all levels of education, to sensitize and inform students to better understand the importance of various environmental resources, such as water resources. This research aims to evaluate the environmental perception of public school students in the city of Campina Grande, Paraíba. The research was carried out in 24 public schools, corresponding to 78% of the total schools, with 1725 students of the 3rd year of High School. Likert model, one on water resources (34 items) and the other on general aspects of environmental perception of students (27 items) were created, validated and applied. The scales were validated using the α-Cronbach test and factorial analysis. In addition to the scales, a questionnaire with 9 open-ended questions was applied. The reliability analysis of both scales indicated the need for rejection of 13 items in the water resources scale, and 6 items in the environmental perception scale, consisting of 21 items each scale and presenting good reliability and internal consistency (α-Cronbach equal to 0.74 and 0.76, respectively). The students are concerned about the preservation of the soil, animals and plants (57,5%, 80,8% and 74,9%), they know the environmental problems of their city (64.8%), however, they consider that they have an illusion of the real truth about environmental problems (49.6%), these data being conflicting, which demonstrates the superficial knowledge that these students possess. They observe that Environmental Education is not adequately treated in the classroom (69.5%), besides not identifying projects focused on this theme at school (41.3%). They consider that their attitudes reflect on all humanity (63.0%) and that hunger and poverty influence environmental problems (62.3%). Regarding Water Resources, in what concerns the aspect of saving water to avoid waste, it is noted that the trend is due to economic reasons, because it is expensive for their parents (71.5%), but they recognize their responsibility in relation to water crisis in the city of Campina Grande, Paraíba (61.6%). They consider important the preservation of plants (83.8%) and soil (88.3%) in order to have quality water resources, however, there were no significant differences in knowing or not the quality of water sources in the city. Based on the results obtained, the students mostly present a prior but superficial knowledge of the subject in focus, which does not allow them to have a critical and reflexive perception of the environmental problems of their community.